METODE SISTEMATIC LITERATUR RIVIEW UNTUK ANALISIS KESESUAIAN PENGEMBANGAN MEDIA BELAJAR PADA KURIKULUM MERDEKA - Faisal Arief Ramadhan; Yusuf Rendi Wibowo; Irfan Irfan; Kharisma Romadhon (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2023)
This study aims to assess the appropriateness of learning resources produced with the use of independent, curriculum-based R&D research. This study falls within the qualitative research category since it makes use of phenomenological methods. The data in this study were examined using the data analysis technique known as the systematic literature review, or SLR (SLR). By employing a systematic literature review strategy, where each step is outlined, researchers may methodically scan reviews and locate articles. Researchers must gather and then filter journal articles from Google Scholar, SINTA, DOAJ, and Scopus in order to finish the study. The articles are then gathered and archived between 2021 and 2022 using the year of publication criterion. 216 articles that are closely linked to the keywords used were chosen by the researchers from a range of publications. The researcher's next step is to gather research and development-related papers as part of a research plan to provide educational materials for a self-contained curriculum. The results of this study are utilized to develop the final conclusions of 15 journal articles that may be employed in an autonomous curriculum for learning at the primary school level. 15 educational resource articles are created using the ADDIE paradigm. Video animations, interactive PowerPoint slide shows, comic books, Macro Media Flash, Android applications, and Articulate Storylines are just a few of the eight various instructional media forms that may be used